Fine‐mapping of two differentiated thyroid carcinoma susceptibility loci at 9q22.33 and 14q13.3 detects novel candidate functional SNPs in Europeans from metropolitan France and Melanesians from New Caledonia. Issue 3 (30th March 2016) - Tcheandjieu, Catherine; Lesueur, Fabienne; Sanchez, Marie; Baron‐Dubourdieu, Dominique; Guizard, Anne‐Valerie; Mulot, Claire; Laurent‐Puig, Pierre; Schvartz, Claire; Truong, Therese; Guenel, Pascal
Abstract : Incidence of differentiated thyroid carcinoma varies considerably between countries and ethnic groups, with particularly high incidence rates in Melanesians of New Caledonia. Differentiated thyroid cancer (DTC) has a familial relative risk higher than other cancers, highlighting the contribution of inherited factors to the disease. Recently, genome‐wide association studies (GWAS) identified several DTC susceptibility loci. The most robust associations were reported at loci 9q22 (rs965513 and rs1867277) and 14q13 (rs944289 and rs116909734). In this study, we performed a fine‐mapping study of the two gene regions among Europeans and Melanesians from Metropolitan France and New Caledonia. We examined 81 single nucleotide polymorphisms (SNPs) at 9q22 and 561 SNPs at 14q13 in Europeans (625 cases/776 controls) and in Melanesians (244 cases/189 controls). The association with the four SNPs previously identified in GWAS was replicated in Europeans while only rs944289 was replicated in Melanesians. Among Europeans, we found that the two SNPs previously reported at 9q22 were not independently associated to DTC and that rs965513 was the predominant signal; at 14q13, we showed that the haplotype rs944289[C]‐rs116909374[C]‐rs999460[T] was significantly associated with DTC risk and that the association with rs116909374 differed by smoking status ( p ‐interaction = 0.03). Among Melanesians, a new independent signal was observed at 14q13 for rs1755774 which is strongly correlated to rs2787423; this latter is potentially a functional variant. Significant interactions with parity ( p  < 0.05) and body mass index were observed for rs1755774 and rs2787423. This study contributed to a better characterization of the DTC loci 9q22 and 14q13 in Europeans and in Melanesians and has identified novel variants to be prioritized for further functional studies. Abstract : What's new? People of Melanesian descent in the South Pacific have an especially high risk of differentiated thyroid cancer (DTC). Certain genetic loci are thought to increase DTC risk. In this case‐control, SNP fine‐mapping study, the authors compared those candidate loci in Europeans and Melanesians in France and New Caledonia. They found that certain novel SNP variants may be worth investigating further for their role in DTC risk.